Improved power quality and reduced losses in DFIG-based WECS using third-order sliding mode control - Belhait, Abdelaziz; Louafi, Messaoud; Ghoudelbourk, Sihem (Institute of Advanced Engineering and Science, 2025)
The study presents a comparative analysis of two advanced high-order sliding mode control (HOSMC) strategies—super-twisting sliding mode control (STSMC) and third-order sliding mode control (TOSMC)—for enhancing the performance of doubly-fed induction generator (DFIG)-based wind energy conversion systems (WECS). The key goals are to maximize energy efficiency, minimize the total harmonic distortion (THD) in the stator current, and reduce electrical losses within the system. Both control strategies are integrated into a direct field-oriented control (DFOC) scheme using space vector modulation (SVM) to improve dynamic response and control accuracy. MATLAB/Simulink simulations show that TOSMC consistently outperforms STSMC in multiple performance aspects. TOSMC ensures better energy efficiency through precise tracking of active and reactive power references while mitigating transient oscillations (chattering effects).Furthermore, TOSMC significantly reduces harmonic distortion, achieving a THD of 0.21%, compared to 0.33% for STSMC, and surpasses conventional controllers, which exhibit a minimum recorded THD of approximately 0.46%. The mitigation of transient phenomena also contributes to reduced switching losses and ohmic heating, thereby enhancing the generator’s thermal stability and overall reliability.